Design on Wind Turbine Performance to Support Sustainable Development: A Systematic Literature Review - Siti Windi Fabian; Ernawati Saptaningrum; Wawan Kurniawan (Universitas Negeri Semarang, 2026)
To achieve the Sustainable Development Goals (SDGs), wind energy optimization is crucial, but it is often ineffective in environments with low wind speeds and high turbulence. This systematic literature review (SLR) examines the impact of wind turbine design modifications on improving aerodynamic performance. This study analyzes peer-reviewed articles from the Scopus database published between 2018 and 2025 using the PRISMA protocol. The selection process focused on physical design interventions, analysis techniques, and quantitative performance parameters. The results show that blade geometry modifications dominate the literature, with research covering conventional optimization approaches as well as emerging strategies such as biomimicry, blade tip engineering, and additive manufacturing materials. Methodologically, Computational Fluid Dynamics (CFD) simulations are predominantly used over purely experimental methods. Overall, the design modifications reviewed showed improvements in power coefficient (Cp) and initial torque characteristics. This study concludes that physical designs tailored to local wind conditions are crucial for maximizing wind energy potential in areas with limited resources.